Bắc Kỳ các tỉnh toàn đồ (2017)
91 trang Bản đồ 14 tỉnh Bắc Kỳ: Cao Bằng, Lạng Sơn, Thái Nguyên, Bắc Ninh, Sơn Tây, Hưng Hóa, Tuyên Quang, Quảng Yên, Hải Dương, Hưng Yên, Nam Định, Hà Nội, Ninh Bình, Thanh Hóa